Lymph transport in rat mesenteric lymphatics experiencing edemagenic stress - Rahbar, Elaheh (2014)
OBJECTIVE: To assess lymphatic flow adaptations to edema, we evaluated lymph transport function in rat mesenteric lymphatics under normal and edemagenic conditions in situ. METHODS: Twelve rats were infused with saline (intravenous infusion, 0.2 ml/min/100g body weight) to induce edema. We intravitally measured mesenteric lymphatic diameter and contraction frequency, as well as immune cell velocity and density before, during and after infusion. RESULTS: A 10-fold increase in lymph velocity (0.1–1 mm/s) and a 6-fold increase in flow rate (0.1–0.6 μL/min), were observed post-infusion, respectively. There were also increases in contraction frequency and fractional pump flow 1-minute post-infusion. Time-averaged wall shear stress increased 10 fold post-infusion to nearly 1.5 dynes/cm(2). Similarly, maximum shear stress rose from 5 dynes/cm(2) to 40 dynes/cm(2). CONCLUSIONS: Lymphatic vessels adapted to edemagenic stress by increasing lymph transport. Specifically, the increases in lymphatic contraction frequency, lymph velocity, and shear stress were significant. Lymph pumping increased post-infusion, though changes in lymphatic diameter were not statistically significant. These results indicate that edemagenic conditions stimulate lymph transport via increases in lymphatic contraction frequency, lymph velocity and flow. These changes, consequently, resulted in large increases in wall shear stress, which could then activate NO pathways and modulate lymphatic transport function.